URGENSI HARMONISASI STANDARISASI HALAL OLEH THE STANDARDS AND METROLOGY INSTITUTE FOR THE ISLAMIC COUNTRIES (SMIIC) DALAM UPAYA MENGURANGI SENGKETA PERDAGANGAN INTERNASIONAL - Intan B Nur Annisa (BELLI AC PACIS, 2020)
This research examines the absence of international halal standards in the interest of the differences in the standards of halal institutions which raises the urgency of halal standard harmonization by Standardization and Metrology for Islamic Countries (SMIIC) as an effort to decrease the international trade dispute. The type of research used in this study is normative with prescriptive analytic to identify the urgency of harmonizing international halal standards and proposing SMIIC as the center of harmonization of international halal standards institutions in terms of conformity with SMIIC international legal organizations and international trade. The result of this research showed the urgency of harmonizing halal product standardization is as a legal certainty of international halal standards, to prevent the overlapping of halal standard, increase consumer confidence, increase food supply integration, reduce time and production costs, and provide conducive of trade situation. SMIIC was proposed as a center for international halal standard harmonization institutions due to several considerations, including related to the urgency of harmonizing international halal standards, SMIIC’s position as an OIC affiliated institution that guarantees authority in issuing international halal standard harmonization, and for the compatibility of SMIIC’s policies with the WTO’s policies precisely of TBT Agreement.